2022
DOI: 10.1177/10888683211073007
|View full text |Cite
|
Sign up to set email alerts
|

Agreeableness and Its Consequences: A Quantitative Review of Meta-Analytic Findings

Abstract: Agreeableness impacts people and real-world outcomes. In the most comprehensive quantitative review to date, we summarize results from 142 meta-analyses reporting effects for 275 variables, which represent N > 1.9 million participants from k > 3,900 studies. Arranging variables by their content and type, we use an organizational framework of 16 conceptual categories that presents a detailed account of Agreeableness’ external relations. Overall, the trait has effects in a desirable direction for 93% of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 302 publications
2
29
2
1
Order By: Relevance
“…It is, therefore, conceivable that regions with a disproportionate number of people high in Agreeableness and Conscientiousness will exhibit greater conformity to local social norms, even when those norms run counter to the advice of health experts. Note further, that Agreeableness is in fact not only related to conformity but also to unassertiveness (Wilmot & Ones, 2022). This suggests that some agreeable people may be unable to deviate from local social norms, such as those opposing mask wearing and social distancing, even if they do not believe in them.…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, conceivable that regions with a disproportionate number of people high in Agreeableness and Conscientiousness will exhibit greater conformity to local social norms, even when those norms run counter to the advice of health experts. Note further, that Agreeableness is in fact not only related to conformity but also to unassertiveness (Wilmot & Ones, 2022). This suggests that some agreeable people may be unable to deviate from local social norms, such as those opposing mask wearing and social distancing, even if they do not believe in them.…”
Section: Discussionmentioning
confidence: 99%
“…Bradley et al (2013) found that the associations of agreeableness with performance might be explained by communication. The role of communication in language subject domains could explain why agreeableness is more beneficial in these subject domains as the demands and/or contextual features of these subject domains may amplify the ways in which agreeableness relates to achievement (e.g., working in a team and less emphasis on results; see Wilmot & Ones, 2022).…”
Section: Agreeablenessmentioning
confidence: 99%
“…A tedious screening will be performed toward chosen literature, where the standard of meta-analysis is applied to emphasize the heterogeneity of the data collected. [35] Software packages such as Excel and R Studio (MetaFOR Library) will be used to analyze the output from the screening. The analysis focuses on graphical, numerical, and text data extraction, model estimation, exploration and quantification of heterogeneity, and meta-regression or correlation between datasets.…”
Section: Meta-analysismentioning
confidence: 99%